2020
DOI: 10.1016/j.trsl.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor treating fields cause replication stress and interfere with DNA replication fork maintenance: Implications for cancer therapy

Abstract: Tumor treating fields (TTFields) is a noninvasive physical modality of cancer therapy that applies low-intensity, intermediate frequency, and alternating electric fields to a tumor. Interference with mitosis was the first mechanism describing the effects of TTFields on cancer cells; however, TTFields was shown to not only reduce the rejoining of radiation-induced DNA double-strand breaks (DSBs), but to also induce DNA DSBs. The mechanism(s) by which TTFields generates DNA DSBs is related to the generation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 74 publications
4
85
0
Order By: Relevance
“…Multiple cytotoxic mechanisms are attributed to TTFields, including their effect upon microtubules and septin fibers of proliferating cancer cells, which disrupts mitosis and causes cell death, mitotic catastrophe, non-viable daughter cells, and cellular stress (6)(7)(8)(9)(10)(11). TTFields also inhibit DNA damage repair (12), enhance replication stress (13), block cellular migration and invasion (14), and increase autophagy (15).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cytotoxic mechanisms are attributed to TTFields, including their effect upon microtubules and septin fibers of proliferating cancer cells, which disrupts mitosis and causes cell death, mitotic catastrophe, non-viable daughter cells, and cellular stress (6)(7)(8)(9)(10)(11). TTFields also inhibit DNA damage repair (12), enhance replication stress (13), block cellular migration and invasion (14), and increase autophagy (15).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, TTFields enhanced cancer cell sensitivity to radiation when cells where exposed to radiation after TTFields delivery, opening up new possibilities for developing novel radiosensitization treatment protocols. Taken together, these data proposed an additional mechanism of action of TTFields in vitro (28,29). Although the biological effects of TTFields have been explored, the full knowledge regarding TTFields biophysical mechanism of action against cancer cells is still likely an area ripe for further investigation.…”
Section: Ttfields and Non-mitotic Cellular Effectsmentioning
confidence: 87%
“…Over the years, several in vitro studies conducted on human cancer cell lines have reported the non-mitotic effects of TTFields (3,16,27). A set of more recent studies have shown that TTFields could render cancer cells less efficient in their DNA damage repair capacity, with cells showing higher DNA damage and replication stress (28,29). Gene expression analysis on a variety of non-small cell lung cancer (NSCLC) cell lines treated with TTFields revealed not only changes in cell cycle and mitosis-related pathways, but also in DNA damage response pathways.…”
Section: Ttfields and Non-mitotic Cellular Effectsmentioning
confidence: 99%
“…Many mechanisms have been put forth to explain how TTFields induce programmed cell death. In one scenario, TTFields interfere with DNA fork replication and induce movement and repositioning of DNA fragments created during replication, leading to widespread disruption of the DNA damage repair and breast cancer 1 (BRCA1)-mediated homologous recombination pathways [35][36][37]. In another, endoplasmic reticulum stress in mitotic cells under the effects of TTFields may trigger adenosine monophosphate-activated protein kinase-dependent autophagy [38] and/or immunogenic cell death [39][40][41].…”
Section: Ttfields-triggered Programmed Cell Deathmentioning
confidence: 99%